What two rational expressions sum to [tex]\frac{4x+2}{x^{2}-9+8 }[/tex] Enter your answer by filling in the boxes. Enter your answer so that each rational expression is in simplified form.

What two rational expressions sum to texfrac4x2x298 tex Enter your answer by filling in the boxes Enter your answer so that each rational expression is in simpl class=

Respuesta :

Answer:

[tex]\frac{4x+2}{x^2 - 9x + 8} = \frac{4x}{(x-8)(x-1)} + \frac{2}{(x-8)(x-1)}[/tex]

Step-by-step explanation:

Given

[tex]\frac{4x+2}{x^{2}-9+8 } = \frac{A}{()(x-1)} + \frac{B}{()(x-8)}[/tex]

Required

Fill in the gaps

Going by the given parameters, we have that

[tex]\frac{4x+2}{x^{2}-9+8 } = \frac{A}{()(x-1)} + \frac{B}{()(x-8)}[/tex]

[tex]x^2 - 9x + 8[/tex], when factorized is [tex](x-1)(x-8)[/tex]

Hence; the expression becomes

[tex]\frac{4x+2}{(x-1)(x-8)} = \frac{A}{(x-8)(x-1)} + \frac{B}{(x-1)(x-8)}[/tex]

Combine Fractions

[tex]\frac{4x+2}{(x-1)(x-8)} = \frac{A + B}{(x-8)(x-1)}[/tex]

Simplify the denominators

[tex]4x + 2 = A + B[/tex]

By direct comparison

[tex]A = 4x[/tex]

[tex]B = 2[/tex]

Hence, the complete expression is

[tex]\frac{4x+2}{x^2 - 9x + 8} = \frac{4x}{(x-8)(x-1)} + \frac{2}{(x-8)(x-1)}[/tex]

Answer:4x+2/x2−9x+8 = −6/7(x−1) + 34/7(x−8)